2014
DOI: 10.1089/apc.2013.0230
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Unexplained White Matter Lesions in HIV Positive Individuals Undergoing Brain Magnetic Resonance Imaging

Abstract: White matter (WM) abnormalities are frequently seen on brain MRI of HIV positive (HIV + ) patients. We aimed to determine the prevalence of unexplained WM abnormalities and their associations with HIV disease and cardiovascular risk factors. We conducted a retrospective, cross-sectional study of brain MRI of HIV + patients conducted between 2004 and 2009 at our center. Clinical and laboratory data were compiled, and images were independently reviewed for WM lesions. Images were obtained from 254 patients: 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Other factors (e.g., diabetes mellitus, body mass index, smoking history, and hypercholesterolemia) were not associated with WMH volume in this sample. We may have lacked power for these investigations given the relatively good health of our sample (e.g., only 11% of HIV+ participants had diabetes), a smaller control sample, and a lack of African American participants, a population where these associations have been reported (Haddow et al 2014; Nyquist et al 2014). Previous investigations have revealed relationships between white matter signal abnormality and both older age and cerebrovascular risk factors (McMurtray et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors (e.g., diabetes mellitus, body mass index, smoking history, and hypercholesterolemia) were not associated with WMH volume in this sample. We may have lacked power for these investigations given the relatively good health of our sample (e.g., only 11% of HIV+ participants had diabetes), a smaller control sample, and a lack of African American participants, a population where these associations have been reported (Haddow et al 2014; Nyquist et al 2014). Previous investigations have revealed relationships between white matter signal abnormality and both older age and cerebrovascular risk factors (McMurtray et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that middle-aged HIV+ men had a higher WMH burden that correlated with cognitive deficits, cardiovascular risk factors, and duration of suppressed CD4 T-lymphocyte counts (Su et al 2016). Prior studies detected no association of WMH burden with HIV disease severity biomarkers such as duration of disease or CD4 T-lymphocyte counts (Bornstein et al 1992; Haddow et al 2014). Instead, white matter abnormalities in HIV have been associated with other medical conditions (e.g., hepatitis C), use of cART, demographic variables (e.g., ethnicity), cardiovascular factors (e.g., hypertension and diabetes), and advancing age (Haddow et al 2014; Morgello et al 2014; Soontornniyomkij et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Although the present finding of increased WMH burden in HIV-infected patients is in agreement with findings from earlier studies, the patient populations in these earlier studies were different. [24,25] In particular, earlier studies included severely immunocompromised patients with detectable HIV viral loads, some of whom had neurological signs and symptoms. Therefore, these earlier findings could not be generalized to the HIV-infected patients included in our study, who have sustained suppressed viral load and immune recovery on cART.…”
Section: Discussionmentioning
confidence: 99%
“…[23] So far, only two studies have specifically studied WMH of presumed vascular origin in HIV-infected patients during the cART era, hereafter referred to simply as WMH. [24,25] These studies reported that WMH were commonly observed in HIV-infected patients. However, as these studies did not include HIV-uninfected controls it is unclear whether their findings were a specific effect of HIV or merely related to aging.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of aging with HIV, comprehending the etiological mechanisms underlying depressive symptomatology is even more challenging due to the greater risk for cardiovascular disease and medical comorbidities associated with longer life expectancy in HIV-infected individuals (Greene, Justice, Lampiris, & Valcour, 2013). WM changes have been associated with medical and demographic variables such as hepatitis C, cART treatment, race, cardiovascular factors and advancing age in HIV-infected patients (Haddow et al, 2014; Morgello, Murray, Van Der Elst, & Byrd, 2014; Soontornniyomkij et al, 2014). Further investigation of the multifactorial nature of neuropsychiatric burden in older PLWH might be of outstanding value to optimize the care of these patients.…”
Section: Discussionmentioning
confidence: 99%